Thermal Cutting Temperature Analysis using Probabilistic FEM - Shahar Sulaiman, Mohd; HP. Manurung, Yupiter; Fadzil, M. (International Journal of Engineering and Technology, 2018)
This paper investigates the capability of probabilistic FEM to predict temperature distribution due to thermal cutting process. The application of transient heat source causes non-uniform temperature distribution across the parent metal that can lead to non-uniform expansion and contraction during heating and cooling cycle. This phenomenon will induce thermal stresses to the workpiece that can subsequently lead to unwanted cutting deformation. Therefore, forecast of temperature distribution is important in order to control the amount of heat required in the cutting process. The temperature prediction was computed by using non-linear thermo-elastic-plastic numerical analysis with isotropic strain hardening which is also known as deterministic FEM. For comparison, another extension simulation which is probabilistic FEM using Monte Carlo method was carried out by varying the input power. In this study, both simulation methods had been executed by using FEM software MSC MARC. The material used for the simulation was low carbon steel C15 with the thickness of 2 mm. Based on the results obtained, it was found out that slight differences of temperature distributions were predicted between both methods. The small observable differences occurred due to the probabilistic method was only executed to fluctuate the input power, while the other process parameters were still unchanged. Nevertheless, the Monte Carlo method was successfully integrated into the normal simulation which then transforming it into probabilistic analysis. Hence, through probabilistic method, reliability on prediction could be increased in which the prediction would be closer to reality.Â Â